THE EFFECT OF PHYSICAL WORK ON URINE COLORS AND HEMATOCRITE CONDITIONS IN HEAT-EXPOSED WORKERS IN DEPOT PASIR MUTIARA BOOM BARU - Riri Anggriawan (Sriwijaya University Learning and Education International Conference, 2018)
This study aims to examine the effect of physical work on urine color and hematocrit levels on heat-exposed workers at Depot Pasir Mutiara Boom Baru. The method in this research is cross sectional study and the sample is sand transporter in the Depot Pasir Mutiara. The sample numbered 65 people, with the inclusion criteria of workers who have worked for more than 2 years and are permanent employees. Measurements of dehydration were done through urine color examination taken after work and blood to determine hematocrite levels, whereas physical work was assessed on the basis of work fatigue analysis using the Subjective Self Rating Test (SSRT) questionnaire. Data were analyzed using chi-square test. Based on urine color examination and hematocrite level, the data obtained were almost whole (95%) of workers were dehydrated, only 5% were not dehydrated. The results of physical work measurements (89%) experienced mild fatigue, 10% experienced moderate fatigue and only 1% experienced severe fatigue. The result of chi-square test showed that there was significant influence between physical work on urine color and hematocrite level (p = 0,00). The results obtained can be said that the physical work affect the color of urine and hematocrit levels in heat-exposed workers in Depot Pasir Mutiara Boom Baru.